1994
DOI: 10.1007/bf00212023
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in a splice-donor site of the APC gene in a family with polyposis and late age of colonic cancer death

Abstract: Adenomatous polyposis coli (APC) is an autosomal dominant disease characterized by the development of hundreds of colorectal adenomatous polyps during the first decades of life. The expression of the disease varies, as the age of onset of colonic cancer and the severity of extracolonic manifestations often differ between affected families. An attenuated form of APC has also been described in which a small number of polyps and a later age of onset of colonic cancer is observed. Cloning of the APC gene has allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 18 publications
2
42
0
2
Order By: Relevance
“…Germline alterations are usually detected in 70% of classic patients with FAP and in 10% of patients with AAPC (Heinimann et al, 2001;Lamlum et al, 2000;Spirio et al, 1993;van der Luijt et al, 1996b). A genotype-phenotype correlation has been observed by several authors, suggesting that clinical variability partially depends on the position of mutations along the gene (reviewed in Fodde and Khan, 1995;Pilarski et al, 1999;Spirio et al, 1993;Varesco et al, 1994;van der Luijt et al, 1995).…”
mentioning
confidence: 96%
“…Germline alterations are usually detected in 70% of classic patients with FAP and in 10% of patients with AAPC (Heinimann et al, 2001;Lamlum et al, 2000;Spirio et al, 1993;van der Luijt et al, 1996b). A genotype-phenotype correlation has been observed by several authors, suggesting that clinical variability partially depends on the position of mutations along the gene (reviewed in Fodde and Khan, 1995;Pilarski et al, 1999;Spirio et al, 1993;Varesco et al, 1994;van der Luijt et al, 1995).…”
mentioning
confidence: 96%
“…A putative alternative start site at codon 184 (exon 5) has been proposed to reinitiate protein synthesis downstream of a 5′ mutation 19 . In addition, it has been suggested that AAPC mutations in exon 9 may produce normal APC protein by alternative splicing 20, 21 . Recently, a recessive form of adenomatous polyposis due to mutations in the MYH gene was described and differentially named "MYH-associated polyposis" 22, 23 .…”
mentioning
confidence: 99%
“…Splicing variants of APC without exon 10, 11 or exon 15 in normal controls have been reported, although their physiological roles are unknown (4 -6). Varesco et al (7) indicated that a splice donor site mutation on exon 10 was associated with late-onset FAP, which is a milder form of the disease. The variant lacking exon 15 has been reported to cause quantitative distortion of mRNA isoforms both in the splice acceptor site mutant and in a germline mutation at the last nucleotide of exon 15 (6).…”
Section: Discussionmentioning
confidence: 99%